Setting Fuel Prices in Jokowi's Era in Light of Adam Smith and Ibnu Taimiyah Pricing Theory - Andriani (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
Fuel oil (BBM) is one of the needs of the Indonesian people, which must be guaranteed when available. So the government plays a vital role in managing. Included in the policy authority for setting subsidised fuel prices, the government determines prices. During Jokowi's administration, which is entering its second term as president, the policy of changing fuel prices has been implemented several times. This study describes the traces of setting fuel prices under Jokowi's administration, using qualitative research with descriptive analysis that describes the problem using existing theory. The theory used in this study is pricing according to classical economists, namely Adam Smith and Islamic economists, namely Ibnu Taimiyah. The results of this study explain that based on Adam Smith's thoughts regarding the theory of pricing, realistic prices operate independently in a free market without interference from the authorities.In contrast, the authority is to determine subsidised fuel prices. So Adam Smith's thinking cannot be applied to conditions of changes in subsidised fuel prices in Indonesia. Meanwhile, according to Ibn Taimiyah, there is a concept of price changes due to demand and supply. The reality is that the increase in fuel prices is not due to supply and demand but budgetary issues. Then the existence of a fair price, according to Ibn Taimiyah, aims to create a sense of fairness for both the seller and the buyer. Through the reasons for managing subsidy targets, the form of fair prices, according to Ibnu Taimiyah, can be used in the current increase in fuel prices.